Comparative Pharmacokinetics and Egg Residues of Amoxicillin, Single and in Combination with Bromhexine, in Laying Hens - Jeong-Won Kim; Ji-Soo Jeong; Jin-Hwa Kim; Chang-Yeop Kim; Eun-Hye Chung; So-Young Boo; Soo-Ha Lee; Je-Won Ko; Tae-Won Kim (Pathogens)
The need for antibiotics in commercial laying hens is increasing owing to intensive farming systems. Amoxicillin trihydrate (AMX), an aminopenicillin β-lactam antibiotic, exerts broad bactericidal activity. However, its short half-life necessitates frequent administration to ensure efficacy, thus limiting its use. Herein, we investigated the effect of concurrent administration of bromhexine hydrochloride (BRM), a mucolytic agent, on AMX pharmacokinetics, performing a comparative pharmacokinetic analysis of AMX administration alone and in combination with BRM. AMX (50 mg/kg) was administered by oral gavage once daily for three days alone or in combination with 10 mg/kg BRM. Plasma and egg samples were collected to evaluate pharmacokinetic profiles and egg residues. The area under the curve and maximum plasma concentration values were significantly higher in the AMX + BRM group than the AMX only group. However, there were no significant differences in AMX half-life in the elimination phase (T1/2), elimination rate constant (kel), or apparent clearance (CL/F) values. In the egg residue study, the withdrawal period for AMX was 5 days in both groups, with no significant difference when using the maximum residue limit (MRL) of 10 μg/kg. The concentration of BRM in the eggs remained at 100 μg/kg up to the fourth day following drug administration. Conclusion: These results confirmed that BRM co-administration increased systemic exposure to AMX, with a negligible residual impact of amoxicillin in eggs.